Relationship Between Knee Mechanics and Time Since Injury in ACL-Deficient Knees Without Signs of Osteoarthritis. (May 2015) - Zabala, Michael E.; Favre, Julien; Andriacchi, Thomas P.
Background: There is increasing evidence that kinematic changes after anterior cruciate ligament (ACL) injury can influence the risk for premature osteoarthritis. However, kinematics can change over time, and the factors influencing those changes remain unknown but potentially important. Hypothesis/Purpose: The purpose of this study was to perform gait analysis on a population of ACL-deficient (ACLD) subjects without knee osteoarthritis after considerable time had elapsed since their injuries. The following hypotheses were tested: (1) ACLD knees will have greater anterior femoral translation, external femoral rotation, and flexion moment as compared with healthy contralateral knees with increased time since injury; (2) side-to-side differences in anterior femoral translation and external femoral rotation are positively associated with side-to-side differences in knee flexion moment. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Nineteen subjects with unilateral ACLD (time since injury, 1-384 months) underwent gait testing. Linear regression testing was performed for significant relationships between side-to-side differences in tibial translation and rotation during stance and the amount of time since injury, as well as the relationship between differences in peak flexion moment and differences in translation and rotation. Results: There was a time dependency in side-to-side differences. Subjects with shorter times since injury had the femur of the ACLD knee more posteriorly translated and internally rotated than the femur of the contralateral knee, and subjects with longer times since injury had the femur of the ACLD knee more anteriorly translated ( R 2 = 0.33) and externally rotated ( R 2 = 0.53) than the femur of the contralateral knee. Additionally, when the population was stratified into 2 subgroups based on time after injury (short-term: 1.4-18.7 months; long-term: 58-383.5 months), a relationship between side-to-side differences in knee flexion moment and side-to-side differences in knee translation and rotation was found for the long-term subgroup. Conclusion: The results of this study provide an understanding of the relationship between kinematics and kinetics of the ACLD knee and the amount of time since injury. They suggest that elapsed time since injury might be an important factor when the function of ACL-injured knees is interpreted as it relates to osteoarthritis.